1988
DOI: 10.1002/mar.4220050106
|View full text |Cite
|
Sign up to set email alerts
|

Self‐referencing as a mediator of the effectiveness of sex‐role portrayals in advertising

Abstract: This research examines the extent to which individuals self‐reference advertising portrayals and the consequences of doing so. A composite self‐referencing measure is developed relative to how self‐referencing has been defined and induced in past research. Individuals who exhibited high levels of self‐referencing of stimulus advertisements elicited more positive attitudes and cognitive responses than those who exhibited low levels of self‐referencing. Self‐referencing was also found to mediate the effect of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 10 publications
0
30
0
2
Order By: Relevance
“…In addition, although prior research finds that selfreferencing generally leads to a positive effect on thought processes (e.g., Burnkrant & Unnava, 1995;Debevec & Iyer, 1988), and this was predicted in Study 1, there also may be conditions under which negative self-referencing may occur. For example, with regard to body size and body attractiveness, women (and men) are generally known to have negative perceptions of their bodies.…”
Section: Studymentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, although prior research finds that selfreferencing generally leads to a positive effect on thought processes (e.g., Burnkrant & Unnava, 1995;Debevec & Iyer, 1988), and this was predicted in Study 1, there also may be conditions under which negative self-referencing may occur. For example, with regard to body size and body attractiveness, women (and men) are generally known to have negative perceptions of their bodies.…”
Section: Studymentioning
confidence: 69%
“…Research in psychology and consumer behavior has demonstrated the importance of framing effects in consumer judgments (e.g., Herr, 1989;Tversky & Kahneman, 1981), and more specifically in the portrayals of women and men in advertising (e.g., Debevec & Iyer, 1988). In the present research, the manner in which female body types (both thin and larger-sized) are perceived should depend on whether traditional stereotypes about women are activated from memory.…”
Section: Instructional Framementioning
confidence: 93%
“…This raises the question of the relative effectiveness of sex role portrayals when compared to the issue of self-referencing or model-audience fit (Debevec & Iyer, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the self influences consumers' sensitivity to product advertisements and information (e.g., Burnkrant & Unnava, 1995;Debevec & Iyer, 1988;Hong & Zinkhan, 1995;Reardon & Moore, 1996). The self also affects motivation for ownership in that people use possessions to express themselves (Fournier & Richins, 1991;Hirschman & LaBarbera, 1990).…”
mentioning
confidence: 98%